Five-year outcomes after state-of-the-art percutaneous coronary revascularization in patients with de novo three-vessel disease: final results of the SYNTAX II study. (7th October 2021) - Banning, Adrian P; Serruys, Patrick; De Maria, Giovanni Luigi; Ryan, Nicola; Walsh, Simon; Gonzalo, Nieves; Jan van Geuns, Robert; Onuma, Yoshinobu; Sabate, Manel; Davies, Justin; Lesiak, Maciej; Moreno, Raul; et al.
Abstract: Aims: The SYNTAX II study evaluated the impact of advances in percutaneous coronary intervention (PCI), integrated into a single revascularization strategy, on outcomes of patients with de novo three-vessel disease. The study employed decision-making utilizing the SYNTAX score II, use of coronary physiology, thin-strut biodegradable polymer drug-eluting stents, intravascular ultrasound, enhanced treatments of chronic total occlusions, and optimized medical therapy. Patients treated with this approach were compared with predefined patients from the SYNTAX I trial. Methods and results: SYNTAX II was a multicentre, single-arm, open-label study of patients requiring revascularization who demonstrated clinical equipoise for treatment with either coronary artery bypass grafting (CABG) or PCI, predicted by the SYNTAX score II. The primary endpoint was major adverse cardiac and cerebrovascular events (MACCE), which included any revascularization. The comparators were a matched PCI cohort trial and a matched CABG cohort, both from the SYNTAX I trial. At 5 years, MACCE rate in SYNTAX II was significantly lower than in the SYNTAX I PCI cohort (21.5% vs. 36.4%, P < 0.001). This reflected lower rates of revascularization (13.8% vs. 23.8%, P < 0.001), and myocardial infarction (MI) (2.7% vs. 10.4%, P < 0.001), consisting of both procedural MI (0.2% vs. 3.8%, P < 0.001) and spontaneous MI (2.3% vs. 6.9%, P = 0.004). All-cause mortality was lower in SYNTAX II (8.1% vs. 13.8%, P = 0.013) reflecting a lower rate of cardiac death (2.8% vs. 8.4%, P < 0.001). Major adverse cardiac and cerebrovascular events' outcomes at 5 years among patients in SYNTAX II and predefined patients in the SYNTAX I CABG cohort were similar (21.5% vs. 24.6%, P = 0.35). Conclusions: Use of the SYNTAX II PCI strategy in patients with de novo three-vessel disease led to improved and durable clinical results when compared to predefined patients treated with PCI in the original SYNTAX I trial. A predefined exploratory analysis found no significant difference in MACCE between SYNTAX II PCI and matched SYNTAX I CABG patients at 5-year follow-up. Graphical Abstract: